Tai Chi During and Post-COVID-19 Pandemic: How Much can it Really Benefit Adolescents? - Zhu, Ethan; Fan, Xiujun (International Journal of Innovative Research in Medical Science, 2023)
Adolescents face pressure from their school studies and college admissions, which results in them constantly experiencing symptoms of stress, anxiety, and depression. These symptoms cause sleep quality and concentration to rapidly corrode, which affects their overall mental health. These symptoms have increased in severity as the COVID-19 pandemic progressed, and if left unattended, they will last for a long period, even during post-covid. For the purpose of finding a practical way to combat these effects caused in general, the impacts of practicing Tai Chi on adolescents' general and mental health, as well as the potential underlying mechanisms involved were systematically reviewed through the last 20 years of research. This review provides information on the efficacy of overall health, feasibility, and fundamental knowledge of the practice of Tai Chi. This information could be considered by schools when planning their curriculum and mental health management to support adolescents during and after the pandemic.